Association of Mu-Opioid Receptor(MOR) Expression and Opioids Requirement With Survival in Patients With Stage I-III Pancreatic Ductal Adenocarcinoma - Zhang, Hao; Qu, Mengdi; Gorur, Aysegul; Sun, Zhirong; Cata, Juan P.; Chen, Wankun; Miao, Changhong (Frontiers in Oncology, 2021)
Background The use of opioids in patients with metastatic pancreatic ductal adenocarcinoma (PDAC) is associated with shorter survival and not dependent on the expression of the mu-opioid receptor (MOR). The role of opioid use and MOR expression in stage I-III PDAC has not been investigated. Methods We conducted retrospective study in patients with stage I-III PDAC. MOR expression and OPRM1 gene expression in tumour tissue and non-tumour tissue was measured. Primary endpoints were overall survival (OS) and disease-free survival (DFS). Secondary endpoints included perineural invasion, intraoperative sufentanil consumption, and length of stay. We performed a subgroup group analysis to evaluate the interaction between levels of MOR expression, amount of opioids use (high versus low) and its association with survival. Results A total of 236 patients were enrolled in this study.There were no significantly difference in OS rates in patients with high versus low levels of MOR (1-year OS: 65.2% versus 70.6%, P=0.064; 3-year: 31.4% versus 35.8%, P=0.071; 5-year: 19.4% versus. 16.2%, P=0.153, respectively) in the tumours. The DFS rates between the groups were no significantly difference. Of note, a high expression of MOR combined with high opioid consumption was associated with poor prognosis in stage I-III PDAC patients. Tumor expressing high levels of MOR show higher rates of perineural invasion. Conclusion MOR is not an independent predictor of poor survival in stage I-III PDAC but associated with perineural invasion. Patients requiring high amounts of opioids intraoperatively show worse outcome if they are expressing high levels of MOR.